2022
DOI: 10.1038/s41419-022-05497-y
|View full text |Cite
|
Sign up to set email alerts
|

BET protein inhibition sensitizes glioblastoma cells to temozolomide treatment by attenuating MGMT expression

Abstract: Bromodomain and extra-terminal tail (BET) proteins have been identified as potential epigenetic targets in cancer, including glioblastoma. These epigenetic modifiers link the histone code to gene transcription that can be disrupted with small molecule BET inhibitors (BETi). With the aim of developing rational combination treatments for glioblastoma, we analyzed BETi-induced differential gene expression in glioblastoma derived-spheres, and identified 6 distinct response patterns. To uncover emerging actionable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(70 reference statements)
1
4
0
Order By: Relevance
“…Subsequently, they have attracted increasing interest as valuable candidates for the clinical treatment of Myc-driven cancer, including GBM [ 17 , 18 , 19 ]. Recent studies have demonstrated that pharmacological BET inhibition is effective in counteracting GBM growth in both in vitro and in vivo models, similar to what has been observed in other tumor models [ 20 , 21 , 22 , 23 ]. However, the molecular mechanisms of BET proteins in GBM tumorigenesis are scarcely understood, and the potential of BET inhibitors in treating GBM is largely unexplored.…”
Section: Introductionsupporting
confidence: 70%
“…Subsequently, they have attracted increasing interest as valuable candidates for the clinical treatment of Myc-driven cancer, including GBM [ 17 , 18 , 19 ]. Recent studies have demonstrated that pharmacological BET inhibition is effective in counteracting GBM growth in both in vitro and in vivo models, similar to what has been observed in other tumor models [ 20 , 21 , 22 , 23 ]. However, the molecular mechanisms of BET proteins in GBM tumorigenesis are scarcely understood, and the potential of BET inhibitors in treating GBM is largely unexplored.…”
Section: Introductionsupporting
confidence: 70%
“…1f ). The epigenetic silencing of MGMT is frequently debated as a clinical biomarker 30 and previous work revealed that JQ1 disturbs DNA damage responses by attenuating MGMT expression in glioblastoma cells 31 . While the different treatment responses are often attributed to somatic mutations in cancer genes, this suggests that DNA methylation can function as a complementary mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The finding is of particular interest since corticosteroids like dexamethasone are frequently used during O6AA therapy, and clinical studies show a negative correlation between use and therapy success [78]. In GBM spheroids, some induction of MGMT was evident, albeit at higher dose levels than used in the studies cited above [79]. The epigenetic regulation of MGMT has been extensively reviewed before [18].…”
Section: Tmz-mediated Upregulation Of Mgmt?mentioning
confidence: 99%
“…An alternative strategy of tumor sensitization through MGMT inhibition is based on targeting bromodomain and extra-terminal tail (BET) proteins, which have been identified as potential epigenetic targets in cancer, including glioblastoma. The inhibition of these epigenetic modifiers was shown to reduce MGMT without affecting MMR protein expression [79]. Actually, an inhibitor of BET (Trotabresib) was shown to have antitumor activity in patients with high-grade gliomas and was well tolerated in the TMZ+RT concomitant and TMZ adjuvant settings [86].…”
Section: Mgmt Inhibition and Chemoprotectionmentioning
confidence: 99%